GIMAP5 maintains liver endothelial cell homeostasis and prevents portal hypertension - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (ROCKEFELLER UNIV PRESS, 2021)
Portal hypertension is a major contributor to decompensation and death from liver disease, a global health problem. Here, we demonstrate homozygous damaging mutations in GIMAP5, a small organellar GTPase, in four families with unexplained portal hypertension. We show that GIMAP5 is expressed in hepatic endothelial cells and that its loss in both humans and mice results in capillarization of liver sinusoidal endothelial cells (LSECs); this effect is also seen when GIMAP5 is selectively deleted in endothelial cells. Single-cell RNA-sequencing analysis in a GIMAP5-deficient mouse model reveals replacement of LSECs with capillarized endothelial cells, a reduction of macrovascular hepatic endothelial cells, and places GIMAP5 upstream of GATA4, a transcription factor required for LSEC specification. Thus, GIMAP5 is a critical regulator of liver endothelial cell homeostasis and, when absent, produces portal hypertension. These findings provide new insight into the pathogenesis of portal hypertension, a major contributor to morbidity and mortality from liver disease. Despite major advances in the diagnosis and treatment of viral causes of hepatitis (Vilarinho and Lifton, 2016), the incidence of chronic liver disease continues to rise worldwide, affecting up to 1.5 billion people globally (GBD 2017 Disease and Injury Incidence and Prevalence Collaborators, 2018) and leading to similar to 2 million deaths annually (Moon et al., 2020). Because the demand for liver transplantation far exceeds the supply of available donor organs, understanding the pathogenesis of advanced liver disease and its complications will be required to develop new therapies to reduce adverse disease outcomes. Portal hypertension-increased hepatic resistance to blood flow entering the liver-is a major contributor to the morbidity and mortality of liver disease owing to development of
Keywords: HEMATOPOIETIC STEM; SURVIVAL